DOP69 Long-term outcome of infantile and very early onset IBD: A multi-center study from the IBD Porto group of ESPGHAN. (21st January 2022) - Guz Mark, A; Aloi, M; Scarallo, L; Bramuzzo, M; Escher, J C; Alvisi, P; Henderson, P; Hojsak, I; Lev-Tzion, R; El-Matary, W; Schwerd, T; Weiss, B; et al.
Abstract: Background: Very early-onset inflammatory bowel disease (VEOIBD) is diagnosed before the age of 6 years while infantile IBD occurs before the age of 2 years. We aimed to assess disease characteristics and long-term outcomes in these populations. Methods: We conducted a retrospective longitudinal cohort study in 21 pediatric centers worldwide. Patients diagnosed with VEOIBD between the years 2008–2018 with at least 2 years of follow-up were included. Results: The cohort included 243 patients (52% males), with median follow-up of 5.8 (IQR 3.2–8.4) years. Median age at diagnosis was 3.3 (IQR 1.8–4.5) years, with 69 (28%) diagnosed before the age of 2 years. Disease was classified as Crohn's disease (CD), ulcerative colitis (UC) and IBD-unclassified (IBDU) in 30%, 59% and 11%, respectively. In patients with UC or IBDU, 75% presented with pancolitis. In patients with CD, 62% presented with isolated colonic disease and 32% with ileo-colonic disease, while 19% had perianal involvement. Genetic testing was performed in 96 (40%) patients [40 (58%) <2 years, 56 (32%) 2–6 years, p=0.001], with monogenic diagnosis identified in 23% (33% and 16%, respectively, p=0.08). The most common findings were mutations in IL10-receptor (5 cases, 23%). Stricturing or penetrating disease was observed in 9 cases (4%). First induction therapies were corticosteroids, 5-aminosalicylic acid (5ASA) and nutritional therapy in 53%, 30% and 11%, respectively. Corticosteroids were more common as first induction in infantile vs. non-infantile IBD (64% vs. 49% respectively, p=0.003). Maintenance therapies included deep immune-suppression (mainly biologics and corticosteroids) in 51%, immunomodulators in 27%, and non-immunosuppressive agents (5-ASA, nutritional therapy and antibiotics) in 22% of patients, with no significant differences between age groups. Compared to patients diagnosed after 2 years of age, patients with infantile IBD presented with higher rates of IBDU, lower levels of hemoglobin and albumin and higher levels of CRP, lower weight (but not height) z-scores, had lower rates of response to first induction therapy and shorter time to hospitalization during follow-up (p<0.05 for all). Colectomy was performed in 11% and diversion surgery in 4% of the cohort, with no significant differences between age groups. No malignancies and nor deaths were observed. At end of follow-up, 85% of patients were in corticosteroid free clinical remission. Conclusion: Patients with VEOIBD, including infantile IBD, have fair long-term outcome with low rates of complications and surgical interventions. Nevertheless, patients with infantile IBD demonstrated more severe clinical features at presentation and a lower response to induction therapy.